Case report: ALK-rearranged spindle and epithelioid cell neoplasms with S100 and CD34 co-expression: Additional evidence of kinase fusion–positive soft tissue tumors - Sheng, Shao-Jie; Li, Ju-Ming; Fan, Qin-He; Liu, Yang; Chen, Shao-Yu; Zhao, Ming; Gong, Qi-Xing (Frontiers in Oncology, 2022)
ALK rearrangements have rarely been reported in S100- and CD34-co-expressing soft tissue neoplasms with lipofibromatosis-like neural tumor (LPFNT) pattern or stromal and perivascular hyalinization, mimicking NTRK-rearranged spindle cell tumors. Here, we reported ALK fusions involving related partner genes in two adult soft tissue tumors with S100 and CD34 co-expression, and conducted a literature review of mesenchymal tumors harboring ALK or other kinase fusions. Case 1 was a 25-year-old female who underwent excision of a soft tissue mass in the anterior thigh region. Morphologically, the tumor was composed of spindle cells adjacent to epithelioid cells embedded in myxedematous and hyalinized stroma, with infiltrative boundary. Spindle cells mixed with inflammatory infiltration resembling inflammatory myofibroblastic tumor (IMT) were seen sporadically. However, brisk mitosis and focal necrosis was also observed, indicating an intermediate-grade sarcoma. In case 2, the left side of the neck of a 34-year-old man was affected. The tumor was composed of monomorphic spindle cells arranged in fascicular growth or patternless pattern, with stromal and perivascular hyalinization. Sparse inflammatory cell infiltration was also observed. Both tumors showed CD34, S100, and ALK-D5F3 immunoreactivity. Next generation sequencing (NGS) test identified a PLEKHH2::ALK fusion in case 1, which was confirmed by RT-PCR and Sanger sequencing, whereas the RT-PCR (ARMS method) test detected an EML4::ALK fusion in case 2. In conclusion, this study expands the morphological and genetic landscape of tumors with S100 and CD34 co-expression harboring kinase fusions, and suggests that kinase fusion–positive mesenchymal neoplasms are becoming an enlarging entity with a variety of morphological patterns.